PENERAPAN PEMBELAJARAN PRACTICAL LIFE UNTUK MENINGKATKAN KEMANDIRIAN ANAK USIA DINI PADA KELOMPOK B DI TK PERTIWI DERODUWUR (Al-Fitrah (Jurnal Kajian Pendidikan Anak Usia Dini), 2025)
Independence in children is very important. Group B early childhood children at Pertiwi Deroduwur Kindergarten should have developed their independence, but there are some children who still need guidance from teachers, and some children's independence has not yet developed. The research aims to find out about independence in early childhood group B at Deroduwur Kindergarten, to find out the application of practical life to increase the independence of early childhood children in group B at Pertiwi Deroduwur Kindergarten, and to find out the supporting and inhibiting factors.The research results show that practical life learning at Pertiwi Deroduwur Kindergarten has gone well. Practical life learning such as taking off/putting on shoes, eating and drinking alone, washing hands, brushing teeth, not being accompanied by parents when in class, having the courage to appear in front of the class, saying please/excuse me/thank you can increase independence optimally.Keywords: Independence, practical life, early childhood